2011
DOI: 10.1523/jneurosci.1076-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Event-Related Response in Visual Cortex Modulates Subsequent Visual Responses in Humans

Abstract: Growing evidence from electrophysiological data in animal and human studies suggests that multisensory interaction is not exclusively a higher-order process, but also takes place in primary sensory cortices. Such early multisensory interaction is thought to be mediated by means of phase resetting. The presentation of a stimulus to one sensory modality resets the phase of ongoing oscillations in another modality such that processing in the latter modality is modulated. In humans, evidence for such a mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 37 publications
5
70
0
Order By: Relevance
“…Stimuli in one sensory modality have been shown to influence ongoing activity cross-modally, e.g., phase resets in visual cortex following an auditory stimulus (e.g. Naue et al, 2011;Romei, Gross, & Thut, 2012). Figure 3A shows that this may be possible here, given that changes in somatosensory alpha occurred after the light, even when no touch was present.…”
Section: Discussionmentioning
confidence: 96%
“…Stimuli in one sensory modality have been shown to influence ongoing activity cross-modally, e.g., phase resets in visual cortex following an auditory stimulus (e.g. Naue et al, 2011;Romei, Gross, & Thut, 2012). Figure 3A shows that this may be possible here, given that changes in somatosensory alpha occurred after the light, even when no touch was present.…”
Section: Discussionmentioning
confidence: 96%
“…However, without cortical involvement, multisensory enhancement does not occur (Sanford et al 2005), and cortical cross-modal interactions in humans do not occur until about 165 ms after stimulus onset in the occipitotemporal ventral stream, and not until about 220 ms in the peri-sylvian cortex (Teder-Sälejärvi et al 2002). More recently, Naue et al (2011) found evidence of auditory effects in frontocentral and occipital cortices about 50-200 ms after the auditory component of audio-visual pairs was presented. These delays in processing multimodal components of simple stimuli support the idea that stimulus onsets are processed before multimodal integration, and unimodal timing phenomena should be rendered intact in multimodal synchrony judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the literature on multimodal processing questions the degree to which early sensory areas are unisensory in nature (Brosch et al 2005;Driver and Noesselt 2008;Ghazanfar and Schroeder 2006). Auditory stimuli appear to facilitate the processing of lowthreshold visual stimuli (Noesselt et al 2010) and enhance early visual cortical responses to visual stimuli (Molholm et al 2002;Naue et al 2011), particularly when auditory and visual stimuli are predictably associated (Baier et al 2006).…”
Section: Role Of Multimodal Processing In the Target-mediated Boost: mentioning
confidence: 99%